THE ROLE OF MUSEUM’S ARCHITECTURE IN ISLAMIC COMMUNITY: MUSEUM OF ISLAMIC ART, DOHA - Alraouf, Ali A. (Journal of Islamic Architecture, 2010)
As we are heading through the second decade of the 21st century, architecture of the Islamic communities is still an unresolved dilemma. In this context, the impact of iconic buildings which claim to represent Islam or provide a contemporary approach to Islamic architecture is crucial on different levels. Therefore, a year after Museum of Islamic Art (MIA) opening in Doha, Qatar, an evaluative perspective of the institution’s development story needs to be sketched. In this essay I will use MIA, Doha as a springboard for a discussion related to the museums of the 21th century. Then, I will try to exploit the findings of this discussion in the assessment and critical review of the museum itself. The assessment will include the ability of contemporary architecture to credibly represent Islamic cultural identity. This essay will analyze how and why community participation in museums is a significant factor in bridging the gap and improving relationship between the two institutions. The social inclusion leads to trust, understanding, a sense of identity, and creating a museum that is more relevant to the community. This essay also give some suggestions on how to build bridges between museums and communities, to provide an opportunity for the people living in such communities, like Gulf ones, to find out about their own heritage and to help them realize that it is through their active participation in museum activities that heritage is kept alive. Considering Qatar’s thrive into a post-oil paradigm where knowledge economy might be the generative force for development, an examination of how MIA is contributing to Qatar’s new vision becomes so relevant.